The impact of public expenditure on "operations and ‎equipment" on economic growth in Algeria using the ECM ‎model - YAGOUB , Mohamed (Dirassat Journal Economic Issue, 2020)
Our research is on the use of public spending as a lever for economic growth. The traditional and new theoretical debates which are exposed in our thesis, show that the theoretical framework suitable for the treatment of this problematic arises from the models of endogenous growth and in particular from the model of Barro "1990" and its extensions. The objective of our study is to identify the effect of public spending on ’equipment and operations’ on economic growth in Algeria, to achieve this we examined a multitude of different models which approached this object, we were able to conclude that Using Econometric Modeling that spending does not influence economic growth.